Rancang Bangun Sistem Keamanan Sepeda Motor Dengan GPS Tracker Berbasis Mikrokontroler dan Aplikasi Android - Mahaputra, I Gusti Agung Made Yoga; Agung, I G A Putu Raka; Jasa, Lie (Majalah Ilmiah Teknologi Elektro, 2019)
Abstract— The motorcycle is one of the most widely used types of transportation in Indonesia. The disadvantage of the motor currently lies in its safety. Motorcycle security system with a Microcontroller-based GPS Tracker and an Android Application function to monitor and control the motorcycle through the Android application. Security system testing with three main tests. Testing of motorcycle safety equipment is done by testing each module. Android application testing is done by running the monitoring and control functions. Testing the communication with the application is done by sending commands from the smartphone to the device. The system can run all commands. Motorcycle safety devices can communicate with Android applications and can detect coordinates. The Simcard operator affects the network installation time on the SIM900A module where Telkomsel has a speed of 6 seconds, M3 has 31 seconds and XL has  310 seconds. There is a difference between the reading value between the actual distance of the motorcycle and the distance of the motorcycle to the instrument reaching 4 meters. Keywords — GPS NEOM8N, Motorcycle, Security System, SIM900A.